1996
DOI: 10.3171/jns.1996.85.1.0163
|View full text |Cite
|
Sign up to set email alerts
|

Primitive neuroectodermal tumor of the median nerve Case report with cytogenetic analysis

Abstract: The authors describe a malignant peripheral primitive neuroectodermal tumor (PNET) that originated in the median nerve in an elderly adult. After the diagnosis was made by biopsy, the patient underwent radical local resection with interpositional vein grafting of the brachial artery. The tumor had the typical appearance of a primitive neural tumor with small, round cells forming rosettes. It stained positively for both the Ewing's sarcoma/peripheral PNET antigen (HBA-71) and neuron-specific enolase, confirming… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

1997
1997
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…Recent studies of the tumours, however, have focused mainly on the lesions in soft tissues or bones without close relation to peripheral nerves. Recently, Akeyson et al reviewed 36 cases of the tumours involving the peripheral nerves in the literature [2]. PNET arising in the cauda equina is rare, and only 6 cases have been reported previously [12,14,15,25].…”
Section: Discussionmentioning
confidence: 98%
“…Recent studies of the tumours, however, have focused mainly on the lesions in soft tissues or bones without close relation to peripheral nerves. Recently, Akeyson et al reviewed 36 cases of the tumours involving the peripheral nerves in the literature [2]. PNET arising in the cauda equina is rare, and only 6 cases have been reported previously [12,14,15,25].…”
Section: Discussionmentioning
confidence: 98%
“…[ 11 ] Aggressive surgical approach had been advocated by most of the earlier cases reported in adults. [ 7 8 ] Similarly, in our case, complete excision was done by sacrificing the involved nerve segment. The gap was bridged by grafting a segment of peroneal nerve.…”
Section: Discussionmentioning
confidence: 78%
“…Extensive search of the English literature revealed only isolated case reports in the adult age group. [ 6 7 8 9 ] The handful of reports also give credence to the fact that intra-neural EES outside the cranio-spinal vault is very rarely reported.…”
Section: Discussionmentioning
confidence: 86%
“…11 Reports of other cases of ESFT originating in the nerves are scarce. Nesbitt and Vidone 12 reported a case of PNET of the sciatic nerve in a 6-year-old patient; Martins et al 13 reported a case of PNET arising from a branch of the sciatic nerve in a 17-year-old female patient; and Akeyson et al 14 described a case of PNET originating in the median nerve of an elderly patient. They are typically fast-growing tumors, usually painful.…”
Section: Discussionmentioning
confidence: 99%